Evaluating the Adoption of Virtual Reality Equine Selection and Judging Curricula: Instructional Responses to a COVID-19 Consequence - Robert Strong; Jennifer Zoller; John Mark Palmer III (Journal of International Agricultural and Extension Education, 2022)
Virtual reality is a technology that is on the leading edge of agricultural sciences dissemination. Virtual reality can be beneficial to improving global food security and better understanding climate impacts, due to its capabilities to reach mass media with critical information. Virtual reality, with the proper access, can connect users from all backgrounds to an immersive experience at their will. The impact of virtual reality as a dissemination tool in agriculture studies is relatively unknown in the literature. Therefore, the researchers chose to implement a mixed-methods research study to investigate the outcomes of student learning in a virtual reality course within the Texas A&M University Equine selection and judging team. Twelve students were purposively sampled within this study, with students taking the course in both 2020 and 2021. Findings from this study suggested that virtual reality could help students reach their desired learning outcomes. Students were also able to provide necessary information on improvements for the course, as it could possibly be a future barrier for student use if headsets are uncomfortable. Another finding of this research is that it further proved virtual reality technologies can be resourceful for disseminating agriculture education. Future studies should look to investigate virtual reality technologies and agriculture education on a wider array, as the results generated from this study are only applicable to the sample.
Keywords: educational technology; horse judging; assessment; diffusion; learning outcomes